Pemanfaatan aplikasi Quizwhizzer untuk meningkatkan kemampuan matematika siswa pada model pembelajaran berbasis game - Yanuarto, Wanda Nugroho; Susanti, Luthfiana Milla (Universitas PGRI Kalimantan, 2023)
In today's technologically advanced classrooms, interaction between students and teachers can be facilitated with the help of QuizWhizzer. In the context of a game-based learning approach, a descriptive study methodology was utilized to investigate students' responses to educational games like QuizWhizzer. Beginning with the preparation of learning tools to direct classroom activities is the first step in the processes for this study. QuizWhizzer preparation, integration, and evaluation. As the teacher's understanding grows, they may realize the shortcomings of the previous gathering and decide to improve it by incorporating the model learning game-based learning they developed with QuizWhizzer. The results of this study are as follows: 1) the learning implementation shows that the teacher is always trying to maximize productivity to improve students' math skills; 2) students' activities during the learning process improved significantly; and 3) the teacher's understanding grows, the students' activities during the learning process improved the students in their education assist others who are further behind them in developing the game and the dialogue.